1881 Ark. Acts 192 - (:unkn) unknown (My University, 1881)
An Act to Preserve the Public Peace and Prevent Crime, ch. XCVI (96), § 3: Prohibited selling, bartering, exchanging, disposing of, or furnishing any dirk, Bowie-knife, sword, spear-cane, brass or metal knuckles, any pistol, or any cartridge for any pistol. Violators guilty of a misdemeanor.
Keywords: TRANSFER